The concordance of triglyceride glucose index (TyG index) and homeostatic model assessment for insulin resistance (Homa-IR) in non-diabetic subjects of adult Indonesian males - Makbul Aman; Dewi Resnawita; Haerani Rasyid; Hasyim Kasim; Syakib Bakri; Husaini Umar; Nu'man AS. Daud; Arifin Seweng (Elsevier, 2021)
Background: Recently, an examination with the TyG index has developed as an alternative to the gold standard, by which this measurement has a relatively high sensitivity in assessing IR. The measurement with TyG index only requires triglyceride levels and fasting blood glucose and is expected to be an examination instrument used to assess IR available in all health facilities in developing countries, especially in Indonesia. In this study, we analyzed the concordance between the TyG index and HOMA-IR in assessing IR in nondiabetic subjects of adult Indonesian males. Method: A cross sectional study was conducted at the outpatient installation of Wahidin Sudirohusodo Hospital and Hasanuddin University Hospital during March until June 2019. An examination of FBG, TyG and fasting insulin was performed. The statistical test results were considered significant if the p value was <0.05. Result: Of the 88 healthy male subjects, the mean age was 51.15 ± 6.8 years. The ROC curve showed that the cut-off value of the TyG index in predicting HOMA-IR was 4.66, with the sensitivity of 86.2% and specificity of 44.1%. The OR value revealed that subjects with a TyG index of ≥4.66 indicated a 5-time greater risk for IR than subjects with a TyG index <4.66. Conclusion: There was a significant concordance between the TyG index and the HOMA-IR in the subjects of adult Indonesian males.